Bubble blasts! An adaptation for buoyancy regulation in shallow foraging gray whales - Bird, Clara; Pirotta, Enrico; New, Leslie; Bierlich, K. C.; Hildebrand, Lisa; Fernandez Ajó, Alejandro; Torres, Leigh (Ecology and Evolution, 2024)
Funding: Data collection was supported by the NOAA National Marine Fisheries Service Office of Science and Technology Ocean Acoustics Program [2016 and 2017; 50-27], the Oregon Sea Grant Program Development funds [2018; RECO-40-PD], the Oregon State University Marine Mammal Institute [2019], and the Office of Naval Research Marine Mammals and Biology program [2020–2022; #N00014-20-1-2760]. Foraging efficiency is key to animal fitness. Consequently, animals evolved a variety of kinematic, morphological, physiological, and behavioral adaptations for efficient locomotion to reduce energy expenditure while moving to find, capture, and consume prey. Often suited to specific habitat and prey types, these adaptations correspond to the terrain or substrate the animal moves through. In aquatic systems, adaptations focus on overcoming drag, buoyancy, and hydrostatic forces. Buoyancy both benefits and hinders diving animals; in particular, shallow divers constantly contend with the costs of overcoming buoyancy to dive and maintain position. Pacific Coast Feeding Group (PCFG) gray whales forage in shallow habitats where they work against buoyancy to dive and feed using various foraging tactics. Bubble blasts (underwater exhalations) have been observed during several foraging tactics performed by PCFG whales. As exhalations aid buoyancy regulation in other diving animals, we hypothesize that bubble blasts are performed by longer, more buoyant whales in shallower water and that bubble blasts increase dive duration while accounting for size and tactic. We test our hypotheses using Bayesian linear mixed effects models and a 7-year dataset of drone footage containing concurrent individual morphological and behavioral data. We find that while headstanding – a stationary, head-down tactic – bubble blasts are performed by longer, more buoyant whales and extend the dive duration, whereas whales using forward-swimming tactics are less likely to bubble blast. Our results suggest that PCFG gray whales may use bubble blasts as a ...